Evaluation of Arthroscopic Bankart Repair and Open Latarjet Technique for Treatment of Recurrent Shoulder Dislocation - Yousaf Gul, Muhammad Zubair Farooq, Inamullah, Muhammad Asghar Essa, Shafaat Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Arthroscopic Bankart repair and open Latarjet procedures are the most frequent surgical treatments for shoulder instability and recurrent shoulder dislocation. Objectives: Therefore, we performed research to assess the clinical outcomes and recurrence rate of instability between both Arthroscopic Bankart repair and open Latarjet techniques. Methods: A cross-sectional study was performed at Lahore General Hospital, Lahore from 2021-23, comprising 74 patients, managed surgically for the condition of recurrent shoulder dislocation. The patients were allocated into two groups viz Group A and B comprising 37 patients in each, who were managed through Arthroscopic Bankart repair and open Latarjet techniques, respectively. Post-operative complications, re-occurrence and success rate were measured in terms of SSV scores. Results: Average age of patients in Arthroscopic Bankart group was 28.34+5.31 years while in open Latarjet group; it was 29.09+6.19 years. 14 (37.83%) patients of Arthroscopic Bankart repair group revealed recurrent shoulder dislocation, while no such complaint was found in the open Latarjet technique. Twenty-seven patients of Arthroscopic Bankart group showed satisfaction with the procedure and 33 out of 37 patients (89.18%) were satisfied with open Latarjet technique. Patients in open Latarjet technique group showed successful recovery of shoulder dislocation and their SSV was 87.91%, while the patients in Arthroscopic Bankart repair group showed less SSV score of 59.76%. Conclusion: Open Latarjet group patients had a greater rate of functional satisfaction, while the arthroscopic Bankart repair group showed a trend for more recurrence. Open Latarjet operation had a higher success rate and patients had a better rate of return to previous top-level sports than Arthroscopic Bankart technique. Keywords: Latarjet; Re-occurrence; Shoulder dislocation; Sports medicine; Surgical complications.